Redução de sódio em snacks extrusados: um estudo baseado no consumidor - Vicenzi, Caroline Balensiefer (2021)
The relationship between the incidence of chronic diseases and high sodium intake has led associations and governments around the world to encourage the food industry to reduce sodium in processed foods, such as extruded corn snacks. As a result, different strategies for reducing sodium have been investigated, with little effectiveness in maintaining consumer acceptability. One of the most effective policies is to adapt the taste by gradually reducing sodium. In this strategy, a sensory analysis with consumers is an extremely important tool. In this context, the present work aimed to develop and validate a methodology for adapting the taste with sodium reduction. 104 were selected to participate in the research and answered an online questionnaire involving sociodemographic data and sodium consumption habits. Based on the responses to this questionnaire, the snacks found were cheese flavor and moon shape. Consumers received two formulations per fortnight over the course of 4 fortnights and performed the paired comparison, acceptability and CATA test. The sodium reduction factor was 5% every fortnight, only in the last fortnight, for comparison purposes, it was provided initially and the other with 15% sodium reduction. The initial formulations and with the maximum sodium reduction (15%) obtained were subjected to physical-chemical characterization. Two consumer segments were obtained through cluster analysis. One of them with healthier habits (cluster 2), and the other with less healthy habits. The sodium reduction factor used (5%) every fortnight was assertive, and consumers were unable to understand which was the saltiest sample in the paired comparison test. In both clusters, the acceptability of the flavor attribute was maintained, even with sodium reductions over the fortnight. The correspondence analysis was performed, however, the chi-square test did not match (p> 0.05) the formulations with the attributes, allowing to state that there were no differences in the sensorial map of the control formulations with the formulations with greater reduction sodium (15%). The necessary physical-chemical characterization that the reduction of sodium had no impact on either water activity or fracture. The colorimetric coordinates dissipated statistics, however, visually, imperceptible. The gradual sodium reduction strategy is effective, but the importance of assessing the segments of the target consumer is emphasized. The results obtained in this study contribute to the advancement of sensory and consumer science.